Pheochromocytoma metastasis to the central nervous system: a case report and systematic review - Fercho, Justyna Małgorzata; Chasles, Oskar G.; Chamier-Gliszczyński, Jakub; Płaza, Dominik Ryszard; Jabłoński, Bogdan; Kokot, Klaudia; Mielczarek, Maciej; Małłek-Grabowska, Małgorzata; Szypenbejl, Jacek; Szkudlarek, Adrian; Szmuda, Tomasz; Siemiński, Mariusz; et al. (Frontiers in Endocrinology, 2025)
BackgroundPheochromocytoma (PCC) is a rare neuroendocrine tumor, with 10–15% of cases showing malignant behavior defined by metastatic spread, including exceptionally rare central nervous system (CNS) involvement. Brain metastases present unique diagnostic and therapeutic challenges due to their potential to impair neurological function. This study reports a case of malignant PCC (mPCC) with CNS metastases and a systematic review to clarify the clinical patterns, management strategies, and prognostic factors.MethodsWe describe the surgically managed case of a 41-year-old man with right frontoparietal brain metastasis. A systematic review, adhering to the PRISMA 2020 guidelines, searched PubMed, Scopus, and Web of Science for peer-reviewed studies on mPCC with brain or spinal metastases confirmed by radiology or histopathology. Data on demographics, symptoms, imaging, treatments, and outcomes were extracted and descriptively analyzed using Python-generated graphics.ResultsThis review identified 18 cranial (1948–2022) and 60 spinal (1977–2024) metastasis cases from 53 studies. Cranial metastases were present at a mean age of 46.6 years (SD 14.1), commonly with headaches (44.4%) and neurological deficits, such as weakness, presented in our case, with 72.2% surgically treated. Spinal metastases occurred at a mean age of 44.5 years (SD, 16.0), often with hypertension (51.7%) or pain, with a mean of 1.7 lesions (SD 1.5). The patient achieved short-term symptom relief post-resection, but incomplete follow-up (33.3% cranial) and reporting gaps (63.3% spinal laterality) limited the prognostic insights. MRI and PET improved the diagnostic accuracy over historical non-contrast CT use (41.7% spinal cases).InterpretationCNS mPCC metastases are exceedingly rare with distinct neurological (cranial) and structural (spinal) presentations. Advanced imaging, particularly magnetic resonance imaging (MRI) and positron emission tomography (PET), is critical for accurate diagnosis and surgical planning. Sparse data underscores the need for registries and prospective studies to standardize care and improve outcomes.